Edukasi Stimulasi Pijat Tui Na dan Oromotor sebagai Strategi Promotif Pencegahan Stunting di Posyandu - Ni Komang Erny Astiti; Ni Gusti Kompiang Sriasih; Made Widhi Gunapria Darmapatni; Ni Wayan Suarniti; Ni Made Dwi Purnamayanti; Asep Arifin Senjaya (LOSARI DIGITAL, 2026)
Tui Na and Oromotor massage education is a promotive strategy to prevent stunting for cadres at Posyandu, so that it optimally educates mothers of child with difficulty eating. Objective: to improve the knowledge and skills of Tui Na and Oromotor massage. Activities include planning (preliminary study, instrument preparation); implementation (pretest, demonstration with phantom and E Module) and evaluation (posttest). The instruments are questionnaire, a checklist for skill, E Module of Tui Na and Oromotor massage and phantom. The knowledge score before and after the activity was analyzed with Wilcoxon, the result significant increase (p = 0.00). Skill scores also similar with knowledge. The modification of Tui Na and Oromotor Massage Education as a Promotive Strategy for Stunting Prevention in Posyandu with demonstrations, phantom and E Module effective in improving the knowledge and skill. The development of cadre competencies in child care with interactive learning media, is the main strategy to support cadres’s roles in the community.